2020
DOI: 10.3389/fmicb.2020.00313
|View full text |Cite
|
Sign up to set email alerts
|

Plants and Associated Soil Microbiota Cooperatively Suppress Plant-Parasitic Nematodes

Abstract: Disease suppressive soils with specific suppression of soil-borne pathogens and parasites have been long studied and are most often of microbiological origin. As for the plant-parasitic nematodes (PPN), which represent a huge threat to agricultural crops and which successfully defy many conventional control methods, soil progression from conducive to suppressive state is accompanied by the enrichment of specific antagonistic microbial consortia. However, a few microbial groups have come to the fore in diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
128
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(133 citation statements)
references
References 138 publications
(201 reference statements)
1
128
0
4
Order By: Relevance
“…Above 12 compostpeat mixtures, only CM -10% was able to suppress PHC, due to its microbial composition that can play a major role in its suppressiveness (Reuveni et al, 2002;Tilston et al, 2002;Papasotiriou et al, 2013;De Corato et al, 2019). The mycobiota composition of the CM -10% treated pots clustered separately if compared to CC and UC, confirming that beneficial microorganisms present in CM -10% treatment can protect the plant root system by microbiota modulation (Antoniou et al, 2017;Mwaheb et al, 2017;Cucu et al, 2019;Topalović et al, 2020;Zhang et al, 2020). Further investigations should be necessary to obtain a deeper understanding of how this protection is conferred because the complex interaction between rhizosphere, microbiota and pathogens is less explored.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Above 12 compostpeat mixtures, only CM -10% was able to suppress PHC, due to its microbial composition that can play a major role in its suppressiveness (Reuveni et al, 2002;Tilston et al, 2002;Papasotiriou et al, 2013;De Corato et al, 2019). The mycobiota composition of the CM -10% treated pots clustered separately if compared to CC and UC, confirming that beneficial microorganisms present in CM -10% treatment can protect the plant root system by microbiota modulation (Antoniou et al, 2017;Mwaheb et al, 2017;Cucu et al, 2019;Topalović et al, 2020;Zhang et al, 2020). Further investigations should be necessary to obtain a deeper understanding of how this protection is conferred because the complex interaction between rhizosphere, microbiota and pathogens is less explored.…”
Section: Resultsmentioning
confidence: 86%
“…Among the various organic amendments, compost has been studied the most and has been used because of its suppressiveness activity (Pugliese et al, 2015;Bonanomi et al, 2018). The phenomenon of suppressiveness is the ability to limit or avoid the spread of a disease where both susceptible crop variety and pathogen are present in the field; this is connected with the available amount or the addition of organic matter and the ability of the seeds and roots to establish a connection with diverse microorganisms present in the soil that uptake exudates and, consequently, limit the outbreak of pathogens and parasites (Topalović et al, 2020).…”
mentioning
confidence: 99%
“…However, both organisms also affect each other indirectly through their effects on the host or each other. Rhizobia as well as a number of other soil bacteria often contribute to preventing plant infection by parasitic nematodes, and this can involve changes in plant (systemic) defenses, root exudates that affect both organisms, while some bacteria and fungi can also directly kill or trap nematodes ( Topalović et al., 2020 ). Thus, we were interested to see what effect rhizobia had on nematode gall formation and if this was controlled by any of the selected nodulation genes.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the number of galls formed were influenced by concurrent inoculation with rhizobia, however, this was only significant in WT plants. The observed drop in gall numbers in rhizobia-coinoculated roots could be due to changes in defense, exudation or other responses in the root induced by rhizobia ( Zamioudis and Pietersé, 2012 ; Topalović et al., 2020 ), but it could also be due to resource competition of the established organs, as both nodules and galls act as nutrient sinks in the root ( Carneiro et al., 1999 ; Voisin et al., 2003 ). While resource competition between nodules and galls could account for the drop in galls in WT roots, this drop was not seen in other genotypes that nodulated even better, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of this plant parasite, and its close ties with its cohabiting microbiome, microbial ecology studies utilizing deep sequencing approaches are a handful. Only a few studies have attempted to characterize the taxonomic and functional core microbiota [34,35] , or tie the microbial community composition in the soil or plant with RKN suppressiveness [36][37][38][39] . In such studies, temporal dynamics of the microbiome in each of the various niches the nematode occupy at its different life stages, or along the crop season, is not often considered.…”
Section: Introductionmentioning
confidence: 99%